Ibrutinib for the treatment of Bing-Neel syndrome, a complication of Waldenström macroglobulinemia: Patient case report. (September 2019) - Hartsell, Lauren; Janes, Amanda; Larck, Chris; Park, Steven; Arnall, Justin R
Bing-Neel syndrome is a rare complication of Waldenström macroglobulinemia, characterized by infiltration of lymphoplasmacytic cells to the central nervous system. Multiple treatment modalities exist including purine analogs, bendamustine, high-dose methotrexate, or high-dose cytarabine. Of interest, ibrutinib, a Bruton tyrosine kinase inhibitor has also displayed efficacy in Bing-Neel syndrome. Current literature is limited for the treatment of Bing-Neel syndrome considering its rarity, and while ibrutinib is indicated for the treatment of Waldenström macroglobulinemia, it is utilized off-label for treatment of Bing-Neel syndrome. Additionally, debate exists regarding the recommended dosing strategy for ibrutinib for this indication with disease remission demonstrated at 560 mg and 420 mg. We present a case report that provides additional evidence for this debate with a patient who received 560 mg of ibrutinib initially and maintained disease control despite a dose reduction to 420 mg for tolerability. Ultimately, more data are needed to develop standardized Bing-Neel syndrome treatment strategies with specific consideration to the use of ibrutinib in this condition.